2018
DOI: 10.14196/mjiri.32.46
|View full text |Cite
|
Sign up to set email alerts
|

A Successful implementation of an idea to a nationally approved plan: Analyzing Iran's National Health Roadmap using the Kingdon model of policymaking

Abstract: Introduction: Hospital beds, human resources, and medical equipment are the costliest elements in the health system and play an essential role at the time of treatment. In this paper, different phases of the NEDA 2026 project and its methodological approach were presented and its formulation process was analysed using the Kingdon model of policymaking. Methods: Iran Health Roadmap (NEDA 2026) project started in March 2016 and ended in March 2017. The main components of this project were hospital beds, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…In the study by Hashemi et al in Iran in 2016, the rate of midwifery per 100,000 of the population in Ilam province was among the highest in the country (n=51) followed by Mazandaran (n=48) and Semnan (n=48). 25 In their study about the inequality in the distribution of healthcare resources in Iran, Lofty et al found that the highest ratio of manpower number per 1000 population was in Ilam province. 29 It should be mentioned that this study does not consider the misdistribution of health workers within Ilam province.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Hashemi et al in Iran in 2016, the rate of midwifery per 100,000 of the population in Ilam province was among the highest in the country (n=51) followed by Mazandaran (n=48) and Semnan (n=48). 25 In their study about the inequality in the distribution of healthcare resources in Iran, Lofty et al found that the highest ratio of manpower number per 1000 population was in Ilam province. 29 It should be mentioned that this study does not consider the misdistribution of health workers within Ilam province.…”
Section: Discussionmentioning
confidence: 99%
“…This common criterion is used for the calculation of workload and the number of employees needed to do it. 25 Studies show that FTE in Iran for midwifery, general medicine and nursing were all >1 (1.2, 1.28 and 1.39, respectively). In this study, to predict the demand for the health workforce in 2026, the FTE was therefore considered as 1.2 for these three job titles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing resources takes time and requires a large investment. Human resources are one of the most important inputs of the healthcare system, having a large impact on public health outcomes and constituting the bulk of funding in the health sector (Hashemi et al, 2018). Based on the interviews and document analysis, the District General Hospital of Dr. (H.C.) Ir.…”
Section: Resourcementioning
confidence: 99%
“…[ 11 ] Successful balanced expansion of the quantity of available ophthalmologists which requires substantial investment and continued research is a prerequisite for enhancing the ophthalmic care services system and improving public health outcomes. [ 9 , 11 ]…”
Section: Introductionmentioning
confidence: 99%